2005
DOI: 10.1074/jbc.m500345200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C βII Plays an Essential Role in Dendritic Cell Differentiation and Autoregulates Its Own Expression

Abstract: Dendritic cells (DC) arise from a diverse group of hematopoietic progenitors and have marked phenotypic and functional heterogeneity. The signal transduction pathways that regulate the ability of progenitors to undergo DC differentiation, as well as the specific characteristics of the resulting DC, are only beginning to be characterized. We have found previously that activation of protein kinase C (PKC) by cytokines or phorbol esters drives normal human CD34؉ hematopoietic progenitors and myeloid leukemic blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 76 publications
(78 reference statements)
2
73
0
Order By: Relevance
“…It has been reported that modulation of cellular individual PKC activity induces PKC-dependent cell differentiation and cytokine production in many cell types (40). PKC has been reported to play critical roles in mediating progenitor-to-DC differentiation and cytokine production from monocytes/macrophages and DCs (41)(42)(43)(44)(45)(46). In the present study, we found that stable tDCs showing high production of IL-10 were generated by addition of PKCI during the process of maturation from iDCs.…”
Section: Endritic Cells (Dcs) Are a Heterogeneous Population Ofsupporting
confidence: 58%
“…It has been reported that modulation of cellular individual PKC activity induces PKC-dependent cell differentiation and cytokine production in many cell types (40). PKC has been reported to play critical roles in mediating progenitor-to-DC differentiation and cytokine production from monocytes/macrophages and DCs (41)(42)(43)(44)(45)(46). In the present study, we found that stable tDCs showing high production of IL-10 were generated by addition of PKCI during the process of maturation from iDCs.…”
Section: Endritic Cells (Dcs) Are a Heterogeneous Population Ofsupporting
confidence: 58%
“…23,24,26,[28][29][30][31] These results revealed that coordinated expression patterns are lost for several cytokines and enzymes involved in oxidative stress, maintained to a large extent for others, and entirely preserved for extracellular matrix proteins (Table 6). In addition to the loss of correlation with PKCb transcript levels, many of these genes also displayed significant expression differences between autistic and control brains, including TGFb2, MCP1, collagen IV and fibronectin 1 ( Table 6).…”
mentioning
confidence: 78%
“…[15][16][17][18][19] In the immune system, PKCb isoenzymes play a critical role in B-cell receptor-mediated responses, T-cell migration and cytokine secretion, dendritic cell differentiation and monocyte and macrophage functioning. [20][21][22][23][24][25] In the gut, PKCbI and bII are expressed by epithelial cells, where they regulate intestinal permeability and cell proliferation, respectively. [26][27][28] In the kidney, both PKCb isoforms are expressed by mesangial cells and play a major role in diabetic nephropathy and albuminuria, possibly through oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunogenic importance of PKC (likely the PKC␤ isozyme) has been documented previously (3,4,16,34), although the mechanism is not entirely clear. PKC agonists increased CD83 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%